Inscribed stelae fragments and a stela base recently found at Karahan, eastern Turkey, and the problem of Karahan in Urartian epigraphy - Işık, Kenan; Genç, Bülent; Gökce, Bilcan; Kuvanç, Rıfat (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Stelae fragments found at Karahan from the end of the 19th century onwards have an important place in studies of Urartian inscriptions. Works in this field and the continued finds of inscribed stelae during every expedition have raised many questions and problems. In this contribution, we attempt to understand the reasons for the existence of these inscribed stelae and blocks at this site, and the continued increase in their numbers. Karahan’s location in the Lake Van Basin and the possibilities of transport of stelae to the site via various itineraries, including sea routes, are discussed. Possible locations from where the stelae fragments were brought are discussed in terms of toponyms and phrases mentioned in the inscriptions.